Experimental study of saw wood dust (SWD) as partial replacement for fine aggregate with ratio 5%, 10% and 15% - Mohd Hafizuddin, Khairuddin (2017)
Cement, granite and sand are conventional materials that heavily uses in construction industry for concrete production. The river sand which is most commonly used fine aggregate in the production of concrete, poses the problem of acute shortage in many area, whose continued use has stated posing serious problems with respect to its cost, availability and environmental impact. Due to this problem, attempt is being made to use the locally available materials to replace the river sand to produce low cost concrete. Saw wood dust (SWD) has been used in concrete, but not widely. This study focuses on the effect of compressive strength on replacing some weight percentage of fine aggregate with SWD in making an effective design mix of concrete. The main objective of this study is to investigate the flexural and compressive strength of modified mix concrete. The other objective to identify the optimum usage of saw wood dust as partial fine aggregate replacement in concrete. Experimental work was conducted in laboratory to determine the specific strength of SWD as partial fine aggregate replacement in concrete by using cube test and flexural test for 14 days and 28 days concrete. Test was also carried out on the workability of the concrete by using slump test. The results show that the SWD concrete has strong compressive strength. The highest compressive strength obtained were found at control concrete which is 21.242 MPa and 30.699 MPa, while the highest flexural strength also at control concrete which is 6.024 MPa and 6.417 MPa at 14 and 28 days. The trend for both test shows that the strength increase with age of curing but decrease as percentage of SWD increase. The workability decrease as percentage of SWD increase and the result at 0%, 5%, 10% and 15% are 48 mm, 42 mm, 35 mm and 33 mm. From the results, optimum percentage of replacement SWD was between 10% and 15% in volume ratio.